A tomada de decisão no investimento em empresas de base tecnológica - Bertani , Francisco (2015)
The main agents of technological change are the new businesses of high-tech sectors, they stimulate socio-economic development through innovative products and processes. In order to challenge existing technological paradigms, the technology-based firms (TBFs) set new market competition standards, regulating the behavior of the existing players. Due to uncertainty and information asymmetry of their activities, TBFs found in financial restriction a limiter to its development. For TBFs, the venture capital industry has been seen as a relevant financial intermediary, providing capital to companies that would otherwise have difficulty obtaining resources. The investment by venture capital companies is risky, because it has low liquidity and is highly dependent on a small group of entrepreneurs / managers. The selection of which company to invest, is a complex process with significant financial repercussions. Therefore, this is a strategic selection, involving a structured decision-making process. Given this context, a research based on the study method of multiple cases was developed, in which three cases were analyzed through nine semi-structured interviews.The results indicate that there is a structured process of decision-making by the venture capital firms with five key steps: business origin, information search, analysis, negotiation and monitoring. The venture capital firms perform both active and passive prospecting, the network recommendations and the entrepreneurial itself, are important sources of information. At the stage of analysis Venture Capitalist invest more time, four main aspects are evaluated: Marketing, Finance, Business and People. Among the main criteria considered to invest, it stands out companies based on innovative product or service and the profile and experience of the entrepreneur and his team. The valuation of TBCFs is performed using the methodology of discounted cash flow. The investment agreement between the two parties is negotiable, however, due to the minority role played by venture capital firms, they have protection clauses that are irreducible. After performing the investment, monitoring is made with active participation of the Venture Capitalist in the invested company in order to ensure the development of it and better divestment.